2021
DOI: 10.5489/cuaj.7252
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Urological Association clinical practice guideline on testosterone deficiency in men: Evidence-based Q&A

Abstract: In 2013, a comprehensive Canada-wide needs assessment revealed that over 25% of Canadian physicians were uncomfortable with the diagnosis and treatment of TD and identified significant knowledge gaps related to patient management. 4 To address the knowledge gaps, the Canadian Clinical Practice Guideline on the Diagnosis and Management of Testosterone Deficiency Syndrome in Adult Males was published in the CMAJ. 5 As part of its mandate, the guideline was offered as a "living document," to be updated periodical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…16 Multiple national guidelines use elevation in hematocrit as a trigger to stop or change TT in men. TT cessation triggers include 55% from Canadian guidelines, 9 54% from endocrine society guidelines and European urology guidelines, 5,26 and between 50%–54% from American urological guidelines. 10 While the rationale for these cutoffs is not cited in these guidelines, they appear to come from the Framingham heart study, which found an increase in adverse cardiovascular outcomes with a hematocrit of 49% or higher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Multiple national guidelines use elevation in hematocrit as a trigger to stop or change TT in men. TT cessation triggers include 55% from Canadian guidelines, 9 54% from endocrine society guidelines and European urology guidelines, 5,26 and between 50%–54% from American urological guidelines. 10 While the rationale for these cutoffs is not cited in these guidelines, they appear to come from the Framingham heart study, which found an increase in adverse cardiovascular outcomes with a hematocrit of 49% or higher.…”
Section: Discussionmentioning
confidence: 99%
“…The upper limit of safe hematocrit varies between 48% to 55% and is based off population data of individuals who were not taking TT. 5,8–10 To date, no studies have tested whether the presence of polycythemia during TT leads to adverse events as a primary outcome.…”
mentioning
confidence: 99%
“…For TCS started on testosterone replacement therapy, followup should be done to assess biochemical and clinical response. 95,97 • Exogenous testosterone administration is contraindicated in TCS seeking future fertility due to the negative impacts testosterone replacement therapy can have on sperm production. 96,98 • In men with symptoms of TD who wish to preserve future fertility, a referral to fertility specialist should be made for consideration of fertility-preserving therapies, such as selective estrogen receptor modulators, aromatase inhibitors, and human chorionic gonadotropin hormone.…”
Section: Management Recommendationsmentioning
confidence: 99%
“…Current American Urological Association and Canadian Urological Association Guidelines note that while greater study on nontraditional testosterone therapies is needed, both organizations support use of SERMs, especially in hypogonadal men who are interested in fertility preservation, as increases in endogenous serum testosterone production do not impact fertility potential, unlike exogenous hormonal replacement. 6,7 Additionally, men with low or low-normal serum LH levels may also be good candidates for the use of SERMs for management of testosterone deficiency.…”
Section: Recommendations From Othersmentioning
confidence: 99%